Which incentives to increase survey response of secondary school pupils? - Maresa Sprietsma (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
Increasing participation rates in pupil surveys has become an important challenge for empirical educational research. In this paper we investigate whether combining a monetary incentive with a personalised invitation to participate in a survey increases the response rate of secondary school pupils. It is found that pupils who receive a personalised invitation and a monetary incentive are not more likely to participate, nor to participate more quickly following the invitation, than those who received a nonpersonalised invitation and a monetary incentive.
urn:nbn:de:bsz:180-madoc-415574
Keywords: I20; C83; 330; response rate; pupil survey; incentives